On the stiffness and damping characteristics of magnetorheological dampers and their implications for flutter analysis - Rodrigues, Daniel L. [UNESP]; Dowell, Earl H.; Bueno, Douglas D. [UNESP] (IOP Publishing, 2020)
Aeroelastic stability analysis plays an important role during the development of new aircraft. It can affect flight envelope, the aircraft geometry, and the design of components, like control surface actuators, for example. However, the aerial vehicle needs to be designed free of flutter even if the actuators experience failure. For some cases the device can exhibit a dynamic behavior similar to the nonlinear damper. In this context, the present paper discusses the characterization of failed actuators described by a magnetorheological damper (MRD). Linear equivalent parameters of damping and stiffness are extracted from Fourier components at different driven harmonic amplitudes and frequencies of motion. The aeroelastic system stability is evaluated by using an adapted pk-based method. Numerical simulations are carried out in the time domain to demonstrate that this proposed modified pk method allows one to investigate the linear equivalent system to predict the dynamic behavior of the nonlinear system when aMRDis considered.
Keywords: actuator in failure mode; aeroelastic stability; flutter analysis; magnetorheological dampers; stiffness and damping characteristics